Promoting Inclusive Holistic Graduate Admissions in Educational Leadership Preparation Programs - Boske, Christa; Elue, Chinasa; Osanloo, Azadeh Farrah; Newcomb, Whitney Sherman (Frontiers in Education, 2018)
Aspiring and practicing school leaders often identify graduate degrees as playing a significant role in achieving educational access and engaging in building, district-wide, regional, state, and national decision-making regarding practice and policy impacting marginalized populations in K-12 U.S. schools. The rationale behind initiating discourse on graduate student involvement grows out of current policy and reform initiatives requiring increased accountability for improved student performance, especially for children from predetermined “subgroups” due to race, class, native language, ability (i.e., emotional, social, cognitive, physical). The call for more deliberate involvement in understanding graduate admissions also arises in regard to student attrition and retention concerns. Faculty often play an under-examined role as gatekeepers throughout the admissions process. The way in which they understand graduate requirements, holistic evaluation, and merit affords opportunities to positively address significant implications for racial equity and diversity in graduate education. To understand faculty reliance upon graduate admissions criteria that undermine espoused university strategic plans, college-level diversity goals, and programmatic decision-making, four professors across the U.S. explore graduate admissions processes and the significance of implementing holistic admissions criteria. We present a holistic graduate admissions conceptual model for school leadership preparation programs to consider when increasing equity and access for minoritized candidates.